Do you play patience? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
For years a driving force in ACP trade negotiations, he is strongly driven, and quite a driver. Shortly after wowing the seminar's opening session, he sat with Paul Osborn of The Negotiator, the seminar newspaper, and talked frankly about unity, strength